Cell-based measures of viral persistence are associated with immune activation and programmed cell death protein 1 (PD-1)-expressing CD4+ T cells - Hatano, Hiroyu; Jain, Vivek; Hunt, Peter W; Lee, Tzong-Hae; Sinclair, Elizabeth; Do, Tri D; Hoh, Rebecca; Martin, Jeffrey N; McCune, Joseph M; Hecht, Frederick; Busch, Michael P; Deeks, Steven G (The Journal of infectious diseases, 2013)
Studies aimed at defining the association between host immune responses and human immunodeficiency virus (HIV) persistence during therapy are necessary to develop new strategies for cure. We performed a comprehensive assessment of ultrasensitive plasma HIV RNA levels, cell-associated HIV RNA levels, proviral HIV DNA levels, and T cell immunophenotyping in a cohort of 190 subjects in whom HIV levels were suppressed by highly active antiretroviral therapy. The median CD4(+) T cell count was 523 cells/mm(3), and the median duration of viral suppression was 31 months. Cell-associated RNA and proviral DNA levels (but not ultrasensitive plasma HIV RNA levels) were positively correlated with frequencies of CD4(+) and CD8(+) T cells expressing markers of T-cell activation/dysfunction (CD38, HLA-DR, CCR5, and/or programmed cell death protein 1 [PD-1]) (P < .05). Having a low CD4(+) T-cell count despite receipt of virologically suppressive therapy was associated with high cell-associated RNA and proviral DNA levels (P < .01) and higher frequencies of CD4(+) T cells expressing CD38, HLA-DR, CCR5, and/or PD-1 (P < .0001). Cell-based measurements of viral persistence were consistently associated with markers of immune activation and the frequency of PD-1-expressing CD4(+) T cells. Treated patients with a low CD4(+) T-cell count had higher frequencies of PD-1-expressing CD4(+) T cells and cell-based measures of viral persistence, suggesting that HIV infection in these individuals may be more difficult to cure and may require unique interventions.